The Effect of Digital Competence and Knowledge Sharing on Digital Transformation in the Greater Bandung TPT (Textile and Textile Products) Industry - Ruslan Ruslan; Ratri Wahyuningtyas (Journal Of Social Science (JoSS), 2025)
The Industrial Revolution 4.0 encourages companies to carry out digital transformation to increase productivity and maintain existence. The textile and textile products (TPT) industry is one sector that has begun to implement automation in its production processes. This study aims to measure the level of digital competence, knowledge sharing, and digital transformation in the Greater Bandung textile industry. The research used a quantitative approach with a causal study method. Data were collected from 260 respondents working in textile companies in the Greater Bandung area through online questionnaires. Non-probability sampling technique was used to select respondents, while data analysis was conducted using a continuum line for variable description and SEM-AMOS version 24 to test the relationship between variables. Descriptive research results show that employee digital competence is at a competent level, knowledge sharing practices are at an effective level, and the company's digital transformation is at a good level. The results of hypothesis testing show that Digital Competence has a positive and significant effect on Digital Transformation. Knowledge Sharing has a positive and significant effect on Digital Transformation. Simultaneously, Digital Competence and Knowledge Sharing have a positive and significant effect on Digital Transformation. This study confirms the importance of digital competence and knowledge sharing in supporting digital transformation in the textile sector. Companies are advised to develop training programs according to employee needs, improve technological infrastructure, facilitate knowledge sharing, and align digital strategies with business strategies.